Curcumin induces a fatal energetic impairment in tumor cells in vitro and in vivo by inhibiting ATP-synthase activity. (31st May 2018) - Bianchi, Giovanna; Ravera, Silvia; Traverso, Chiara; Amaro, Adriana; Piaggio, Francesca; Emionite, Laura; Bachetti, Tiziana; Pfeffer, Ulrich; Raffaghello, Lizzia
Abstract : The dietary polyphenol, curcumin, inhibits mitochondrial ATP synthase and induces a dramatic drop of ATP and a reduction of oxygen consumption leading to autophagy and apoptosis in an NFκB independent manner reducing xenograft growth and tumor angiogenesis. Abstract: Curcumin has been reported to inhibit inflammation, tumor growth, angiogenesis and metastasis by decreasing cell growth and by inducing apoptosis mainly through the inhibition of nuclear factor kappa-B (NFκB), a master regulator of inflammation. Recent reports also indicate potential metabolic effects of the polyphenol, therefore we analyzed whether and how it affects the energy metabolism of tumor cells. We show that curcumin (10 µM) inhibits the activity of ATP synthase in isolated mitochondrial membranes leading to a dramatic drop of ATP and a reduction of oxygen consumption in in vitro and in vivo tumor models. The effects of curcumin on ATP synthase are independent of the inhibition of NFκB since the IκB Kinase inhibitor, SC-514, does not affect ATP synthase. The activities of the glycolytic enzymes hexokinase, phosphofructokinase, pyruvate kinase and lactate dehydrogenase are only slightly affected in a cell type-specific manner. The energy impairment translates into decreased tumor cell viability. Moreover, curcumin induces apoptosis by promoting the generation of reactive oxygen species (ROS) and malondialdehyde (MDA), a marker of lipid oxidation, and autophagy, at least in part due to the activation of the AMP-activated protein kinase (AMPK). According to the in vitro anti-tumor effect, curcumin (30 mg/kg body weight) significantly delayed in vivo cancer growth likely due to an energy impairment but also through the reduction of tumor angiogenesis. These results establish the ATP synthase, a central enzyme of the cellular energy metabolism, as a target of the antitumoral polyphenol leading to inhibition of cancer cell growth and a general reprogramming of tumor metabolism.